A composite chitosan derivative nanoparticle to stabilize a W1/O/W2 emulsion: Preparation and characterization. (15th March 2021) - Fu, Juanjuan; Zhu, Yinglian; Cheng, Fansheng; Zhang, Shuangling; Xiu, Tiantian; Hu, Yue; Yang, Shuo
Highlights: Hydrochloride-carboxymethyl chitosan (CHC-CMC) nanoparticles (261 nm) were obtained. W2 of 2% CHC-CMC and W1 of 1% sodium alginate were optimal for W1 /O/W2 emulsion. Creaming index (81.6 %) by CHC-CMC was higher than that of Tween (67.4 %) after 30 d. Emulsion dual structure by CHC-CMC was clearer than that by Tween after 30 d. Abstract: For preparing stable water-in-oil-in-water emulsion, the role of nanoparticles in stabilizing the interface is very important. In this study, chitosan hydrochloride-carboxymethyl chitosan (CHC-CMC) nanoparticles were prepared considering electrostatic interactions; then the emulsion was prepared and the stability characteristics in presence of NaCl (0–200 mmol/L) and 30 d storage were studied. CHC-CMC nanoparticles (261 nm) were obtained when the CHC: CMC ratio was 1:2. CHC-CMC formation was verified by FT-IR when a new peak appeared at 1580 cm −1 ; W2 contained 2 wt % CHC-CMC and W1 contained 1 wt % sodium alginate, the creaming index (81.6 %) was higher for the emulsions than Tween 80 (67.4 %) after 30 d. Confocal laser scanning microscopy confirmed the double microstructures, in contrast to the collapse with Tween 80, because the CHC-CMC nanoparticles were densely adsorbing on the oil-water interface. This indicates that CHC-CMC has a stronger ability to stabilize W1 /O/W2 emulsion than Tween 80.